COVID-19: Another Look at Solidarity - Häyry, Matti (Cambridge quarterly of healthcare ethics, 2022)
Is there such a thing as corona solidarity? Does voluntary mutual aid solve the problems caused by COVID-19? I argue that the answer to the first question is “yes” and to the second “no.” Not that the answer to the second question could not, in an ideal world, be “yes,” too. It is just that in this world of global capitalism and everybody looking out for themselves, the kind of communal warmth celebrated by the media either does not actually exist or is too weak to rule out the uglier manifestations of group togetherness, driven partly by the pandemic. I make my point by offering two approaches to understanding what solidarity is. According to the first, it is essentially partiality: “us” against “them.” According to the second, it can be many things, including the impartial promotion of the good of others. I show that the second reading would make it possible for mutual aid to solve the problems caused by COVID-19 and other crises. This would happen at the expense of conceptual clarity, but that is a minor concern. The major concern is that the more natural manifestations of group togetherness are incited by negative feelings. This is par for the course within the narrower reading of solidarity, but it means that the potentially positive ideas of identity, care, communal values, and special relations are displayed in violent confrontation instead of a calm recognition of the threats that most of us face together.